2023
DOI: 10.1590/1519-6984.246579
|View full text |Cite
|
Sign up to set email alerts
|

Normalized difference vegetation index for desiccation evaluation with glyphosate + 2,4-D in magnetized spray solution

Abstract: Water magnetization and geoprocessing are increasingly utilized tools in weed management. Our objective was to study the influence of water magnetization on herbicide efficiency and to verify whether there is a relationship between control scores and the normalized difference vegetation index (NDVI). In the laboratory experiment, water was subjected to magnetization and evaluated with respect to four characteristics. In the field experiment, plots of Brachiaria grass were subjected to treatments in a factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…On the contrary, there were no significant differences between the experimental years (ns; p > 0.05). All herbicide treatments reduced the weed NDVI values across the growing seasons, exactly as found in previous studies [20][21][22]. For the first experimental year, the lowest value (0.48) was recorded in plots treated with nicosulfuron + rimsulfuron + dicamba (T3) at 14 DAT.…”
Section: Herbicide Efficacysupporting
confidence: 86%
“…On the contrary, there were no significant differences between the experimental years (ns; p > 0.05). All herbicide treatments reduced the weed NDVI values across the growing seasons, exactly as found in previous studies [20][21][22]. For the first experimental year, the lowest value (0.48) was recorded in plots treated with nicosulfuron + rimsulfuron + dicamba (T3) at 14 DAT.…”
Section: Herbicide Efficacysupporting
confidence: 86%
“…Research with information extracted from images has revealed high correlations between the indices and different phenotypic characteristics of some crops. In brachiaria grass, a correlation of 0.92 was observed between control (%) and NDVI values extracted using images [48]. In corn, digital images were used to evaluate crop performance [46].…”
Section: Discussionmentioning
confidence: 99%